Surgical Site Infections in Breast Surgery for Primary Cancer: Could it Lead to Different Oncologic Outcome? The Potential of Administrative Data Flows in the Study of a Large Population - N, Fabbri (Archives of Clinical and Biomedical Research, 2020)
Abstract not available in the source database.